OPTIMASI WAKTU DAN BIAYA PROYEK KONSTRUKSI GEDUNG DENGAN METODE TIME COST TRADE OFF (Studi Kasus Proyek Non Struktur Gedung Perkantoran Tiga Lantai Tahap Lanjutan di Kota Bengkulu) - Iqbal Alfayed; Fepy Supriani; Agustin Gunawan (Universitas Bengkulu, 2024)
The research objective was to analyze the most optimal time and cost between the additional of overtime and labor. The data used in this study is from the construction project data of a three floors office building advanced stage in Bengkulu City with non structural groups of work. Research began with project network arrangement and critical path identification using Microsoft Project program, the selected critical activity resources then added with overtime and labor by the Time Cost Trade Off method. The results of the critical path identification showed that there are three critical jobs namely walls plastering 1 : 4 thickness 15 mm, anti-fungal exterior painting and wallpaper that selected to be accelerated in order to shorten the total duration of the critical path. The results showed that the addition of one hour of overtime for the first three days of each critical job accelerated the duration of work by 8.24%, and saved costs by 1.77%. The addition of labor of a worker and a handyman on walls plastering 1 : 4 thickness 15 mm and anti-fungal exterior painting jobs, as well as one handyman on wallpaper job is known to accelerate the duration by 8.24%, and save costs by 0.61%. The addition of overtime results the most optimal time and cost by accelerating the duration for 7 days (8.24 %), and saving the total cost of Rp. 4.245.237,92 (1.77%)